(untitled) (Historia, 2021)
English F.W. Reitz’s struggle for survival in the Netherlands as intransigent Boer leader and his return to South-Africa F.W. Reitz’s irreconcilable attitude towards British paramountcy in South Africa after the Anglo-Boer War led to his deportation, and unsuccessful lecturing tour through the USA (October 1902 - February 1903) and his settling in the Netherlands where his wife and children had already been living since the middle of 1900. The nature of his publications during his stay overseas, his deteriorating health, the hardship of his wife and family and their eventual decision to return to South Africa are critically discussed and analysed on the basis of archival and other sources. Afrikaans F.W. Reitz se onversetlike houding teenoor Britse heerskappy in Suid-Afrika na die Anglo-Boereoorlog het gelei tot sy deportasie en ’n onsuksesvolle lesingtoer deur die VSA (Oktober 1902 - Februarie 1903) en vestiging in Nederland waar sy vrou en kinders reeds sedert die helfte van 1900 gevestig was. Die aard van sy publikasies in hierdie tyd, sy verslegtende gesondheidstoestand, die ontberings van sy vrou en gesin en hulle uiteindelike besluit om na Suid-Afrika terug te keer, word uit argivale en ander bronne krities beskryf en ontleed.